Reperfusion therapy for ST elevation acute myocardial infarction 2010/2011: current status in 37 ESC countries - Kristensen, Steen D.; Laut, Kristina G.; Fajadet, Jean; Kaifoszova, Zuzana; Kala, Petr; Di Mario, Carlo; Wijns, William; Clemmensen, Peter; Agladze, Vaja; Antoniades, Loizos; Alhabib, Khalid F.; De Boer, Menko-Jan; et al. (My University, 2014)
Aims Primary percutaneous coronary intervention (PPCI) is the preferred reperfusion therapy in ST-elevation myocardial infarction (STEMI). We conducted this study to evaluate the contemporary status on the use and type of reperfusion therapy in patients admitted with STEMI in the European Society of Cardiology (ESC) member countries.
Keywords: acute myocardial infarction